Examining the formation of human capital in entrepreneurship: A meta-analysis of entrepreneurship education outcomes - Martin, Bruce C.; McNally, Jeffrey J.; Kay, Michael J. (Journal of Business Venturing, 2013)
Effective human capital formation through the medium of entrepreneurship education and training (EET) is of increasing concern for governments, as EET is growing rapidly across the world. Unfortunately, there is a lack of consistent evidence showing that EET helps to create more or better entrepreneurs. We undertake the first quantitative review of the literature and, in the context of human capital theory, find that there is indeed support for the value of EET. Based on 42 independent samples (N=16,657), we find a significant relationship between EET and entrepreneurship-related human capital assets (rw=.217) and entrepreneurship outcomes (rw=.159). The relationship between EET and entrepreneurship outcomes is stronger for academic-focused EET interventions (rw=.238) than for training-focused EET interventions (rw=.151). We find evidence of heterogeneity in many of our correlations, and recommend that future studies examine potential moderators to more clearly delineate EET effect sizes. We also find a number of methodological weaknesses among the studies analyzed and that those studies with lower methodological rigor are overstating the effect of EET. Recommendations to improve the quality of future work in the field are provided.